Pengaruh Pemberian Sari Buah Kersen terhadap Kadar Asam Urat pada Penderita Hiperurisemia - Mahendra, Himeldah Isa; Arum, Puspito (Jurnal Gizi, 2021)
Hyperuricemia is a health condition characterized by increasing uric acid levels in the body. Jamaican cherry (Muntingia calabura) is vitamin C containing fruit that have lowering-purine effect.The aim of this study was to determine the effect of Kersen (Muntingia calabura) extract on uric acidlevels. This was experimental study with pretest-posttest control group design. Male and female aged above 50 years and not taking vitamins were reqruites as subjects . In this study, the subjects were divided into control and treatment group with the total of 17 subjects for each group. The subjects consume 40.5 grams Kersen. The uric acid level was measured by helath professionals using Easy Touch. The diference of uric acid level were analized using Wilcoxon test  and Man-Whitney test, and the correlation and effect of Kersen were analyzed using Partial Correlation test and LinearRegression Test. The results show that uric acid levels in the treatment group were above normal as well as the control group because at the beginning of the study there were differences in the subject selection of each group. The results show that there is an effect of granting cherry juice to uric acid level ( p 0.004).Keywords: Gout, Hyperuricemia, Cherry Fruit, Vitamin C.